Pengembangan dan Pemberdayaan UMKM Usaha Produksi Kuliner di Desa Kampiri - Prayudhi Fadhillah; Besse Friska; Nurfadillah; Annisa M (YP-SDI Lamaddukelleng, 2024)
This research aims to help MSMEs develop their product businesses, so they can reach a wider market, not just traditional markets but through social media marketing. The method we use in implementing KKLP is through a participatory approach and involving the community in interaction and data collection. A participatory approach is used with community involvement in all phases of the process (Makosky et al., 2010). In line with Fletcher et al., (2015) explain how community involvement in knowledge mobilization can be a benchmark in seeing the reality of life in society. It is hoped that using this method can explore existing information on MSME actors in Kampiri Village. The research results show that regarding the development and empowerment of MSMEs culinary productionbusiness in Kampiri Village through can develop and empower MSMEs in Kampiri Village by increasing promotion and marketing of MSME products and providing facilities and infrastructure.